Duration of SARS-CoV-2 positive in quarantine room environments: A perspective analysis. (April 2021) - Liu, Jie; Liu, Jingwen; He, Zheng; Yang, Zhicong; Yuan, Jun; Wu, Haoying; Zhu, Pingting; Fu, Xuesong; Lin, Yunwan; Zhang, Ying; Zhao, Zhengyang; He, Shiyu; et al.
Highlights: Environmental contamination associated with viral load in respiratory tract. Surface contamination associated with sampling interval time after people left. Moist surfaces more vulnerable to remaining SARS-CoV-2 RNA positive. Strict chemical disinfection strategy important for quarantine rooms. Abstract: Objective: To determine the duration of SARS-CoV-2 persistence in quarantine hotel environments. Methods: 39 Patients confirmed by RT-PCR were included. We collected clinical features, laboratory test results, smear sample information, and quarantine room information. Genome sequencing and phylogenetic analysis were conducted. We analyzed the factors associated with environmental contamination. Result: Among 39 COVID-19 cases, 10 were asymptomatic and 37 were imported from aboard. We collected 271 swab samples from environmental surfaces related to observational patients. Eighteen swab samples from seven patients were positive. The highest contamination rates occurred on cups (100%), followed by hand sink (12.82%), toilet seat and flush (7.89%), telephone (5.56%), bedside table (5.56%), and floor drain (5.41%). The results showed that environmental surface contamination was associated with the clinical cycle threshold values for patients ( P = 0.01) and the sampling interval time after the cases left their rooms ( P = 0.03). The duration of environmental surface contamination was associated with the wet status of the sampling site ( P = 0.01). Conclusion: Our findings showed that environmental contamination might be attributed to the viral load in the respiratory tracts of patients and the sampling interval time after the cases left their rooms. Moist surfaces were more vulnerable to remaining SARS-CoV-2 RNA-positive. Our study highlights the importance of implementing strict chemical disinfection strategies in quarantine rooms.